Equal North: how can we reduce health inequalities in the North of England? A prioritization exercise with researchers, policymakers and practitioners. (20th October 2018) - Addison, M; Kaner, E; Johnstone, P; Hillier-Brown, F; Moffatt, S; Russell, S; Barr, B; Holland, P; Salway, S; Whitehead, M; Bambra, C
Abstract: Background: The Equal North network was developed to take forward the implications of the Due North report of the Independent Inquiry into Health Equity. The aim of this exercise was to identify how to reduce health inequalities in the north of England. Methods: Workshops (15 groups) and a Delphi survey (3 rounds, 368 members) were used to consult expert opinion and achieve consensus. Round 1 answered open questions around priorities for action; Round 2 used a 5-point Likert scale to rate items; Round 3 responses were re-rated alongside a median response to each item. In total, 10 workshops were conducted after the Delphi survey to triangulate the data. Results: In Round 1, responses from 253 participants generated 39 items used in Round 2 (rated by 144 participants). Results from Round 3 (76 participants) indicate that poverty/implications of austerity (4.87 m, IQR 0) remained the priority issue, with long-term unemployment (4.8 m, IQR 0) and mental health (4.7 m, IQR 1) second and third priorities. Workshop 3 did not diverge from findings in Round 1. Conclusions: Practice professionals and academics agreed that reducing health inequalities in the North of England requires prioritizing research that tackles structural determinants concerning poverty, the implications of austerity measures and unemployment.